Dimer of arfaptin 2 regulates NF-kappa B signaling by interacting with IKK beta/NEMO and inhibiting IKK beta kinase activity - You, Dong-Joo; Park, Cho Rong; Furlong, Michael; Koo, Okjae; Lee, Cheolju; Alm, Curie; Seong, Jae Young; Hwang, Jong-Ik (ELSEVIER SCIENCE INC, 2015)
I kappa B kinases (IKKs) are a therapeutic target due to their crucial roles in various biological processes, including the immune response, the stress response, and tumor development. IKKs integrate various upstream signals that activate NF-kappa B by phosphorylating I kappa B and also regulate many proteins related to cell growth and metabolism. Although they function as a heteromeric complex comprised of kinase subunits and an adaptor, these kinases produce distinct cellular responses by phosphorylating different target molecules, suggesting that they may also be regulated in a subtype-specific manner. In this study, arfaptin 2 was identified as an IKK beta-specific binding partner. Interestingly, arfaptin 2 also interacted with NEMO. Domain mapping studies revealed that the C-terminal region, including the IKK beta HLH domain and the first coiled-coil NEMO region were respectively required for interactions with the arfaptin 2 N-terminal flexible region. Overexpression of arfaptin 2 inhibited tumor necrosis factor (TNF)-alpha-stimulated nuclear factor-kappa B (NF-kappa B) signaling, whereas downregulation of arfaptin 2 by small interfering RNA enhanced NF-kappa B activity. Dimerization of arfaptin 2 through the Bin-Amphiphysin-Rvs domain may be essential to inhibit activation of NF-kappa B through multimodal interactions with IKK beta s or IKK beta/NEMO, as ectopic expression of the arfaptin 2 fragment responsible for IKK interactions did not change TNF alpha-stimulated NF-kappa B activation. These data indicate that arfaptin 2 is the first molecule to regulate NF-kappa B signaling by interacting with the functional IKK complex but not by direct inhibiting IKK beta phosphorylation. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: RAC1-INTERACTING PROTEIN; ACTIVATION; PHOSPHORYLATION; COMPLEX; NEMO; TRANSCRIPTION; BINDING; TUMORIGENESIS; PATHWAYS; CANCER